Effects of feeding solid-state fermented wheat bran on growth performance and nutrient digestibility in broiler chickens - A.R. Zhang (Elsevier, 2022)
ABSTRACT: Solid-state fermentation has been used to improve the nutritive value of feed ingredients. In the present study, we investigated the effects of solid-state fermented wheat bran (FWB) on growth performance and apparent digestibility in broiler chickens. We measured the growth performance (ADFI, ADG, feed conversion, livability, and European performance efficiency factor) over 38 d in chicks fed a corn-soybean meal control diet (CON) or CON plus wet FWB (25 g/kg [T1]; 50 g/kg [T2]); or T1 plus 3 g/kg (T3); or T2 plus 6 g/kg (T4) soybean oil). The same diets were used to determine nutrient availability in chicks aged 20 d. Regression equations for AME and AMEn were obtained using 20-day-old chicks fed either the corn-soybean meal basal diet only or basal diet partially substituted with 50, 150, or 300 g/kg DM FWB. Diets containing 25 or 50 g/kg wet FBW did not affect the growth performance of broiler chickens, nor the apparent DM, energy, and nitrogen digestibility of the feeds, compared with the control diets (all P > 0.05). Further supplementation with oil did not improve the growth performance of broiler chickens compared with controls or chickens fed FBW. However, chickens fed diets containing soybean oil (T3 or T4) had lower (P = 0.005 and P = 0.040, respectively) apparent DM and energy digestibility than the control and FWB groups. The regression equations for AME and AMEn with the substitution of FWB produced values of 1,854.3 and 1,743.9 kcal/kg DM, respectively, and the equations were Y = 1854.3X + 52.7 (R2 = 0.971, n = 24, P < 0.001), and Y = 1743.9X + 44.6 (R2 = 0.978, n = 24, P < 0.001), respectively. Supplementation with wet FWB did not affect the growth performance of broiler chickens. Therefore, FWB is a suitable feed component for broilers.